Efficient optical pumping and high optical depth in a hollow-core photonic-crystal fibre for a broadband quantum memory - Sprague, MR; England, D; Abdolvand, A; Nunn, J; Jin, X; Kolthammer, W; Barbieri, M; Rigal, B; Michelberger, P; Champion, T; Russell, P; Walmsley, I (2013)
The generation of large multiphoton quantum states - for applications in computing, metrology and simulation - requires a network of high-efficiency quantum memories capable of storing broadband pulses. Integrating these memories into a fibre offers a number of advantages towards realizing this goal: strong light-matter coupling at low powers, simplified alignment and compatibility with existing photonic architectures. Here, we introduce a large-core kagome-structured hollow-core fibre as a suitable platform for an integrated fibre-based quantum memory with a warm atomic vapour. We demonstrate, for the first time, efficient optical pumping in such a system, where 90 ± 1% of atoms are prepared in the ground state. We measure high optical depths (3 × 104) and narrow homogeneous linewidths (6 ± 2 MHz) that do not exhibit significant transit-time broadening, showing that we can prepare a Λ-level system in a pure state. Our results establish that kagome fibres are suitable for implementing a broadband, room-temperature quantum memory, as well as a range of nonlinear optical effects. © IOP Publishing and Deutsche Physikalische Gesellschaft.